2004
DOI: 10.1002/ange.200353348
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Stereochemical Assignment of Myriaporones 1, 3, and 4

Abstract: The natural products tedanolide (1 a) and 13-deoxytedanolide (1 b), which were isolated by Schmitz et al. [1] and Fusetani et al., [2] respectively, exhibit picomolar activity against a range of cancer cell lines. Their biological activity coupled with their scarcity has prompted considerable synthetic attention.[3] Our interest in these compounds stems from the isolation of a related class of natural products, the myriaporones (2 a-d), reported by Rinehart et al. in 1995. [4, 5] The myriaporones are nearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Yet encouragingly, results were obtained by addition of a nickel complex or salts of copper and palladium (Table 1). Among them, it was found that only copper salts gave significant conversions without counter-anion effects (Table 1, entries [4][5][6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet encouragingly, results were obtained by addition of a nickel complex or salts of copper and palladium (Table 1). Among them, it was found that only copper salts gave significant conversions without counter-anion effects (Table 1, entries [4][5][6].…”
Section: Resultsmentioning
confidence: 99%
“…[2] on treatment with various reagents, such as aryl isocyanates, [3][4][5][6][7][8][9] inorganic [10,11] and organic [12][13][14][15] chlorides or organic anhydrides, [16,17] in the presence of a dipolarophile and often a base, the isoxazole derivatives are produced besides the discarded material derived from the reagent employed [Eq. (1)].…”
Section: Introductionmentioning
confidence: 99%
“…For the final epoxidation we intended to use unprotected lactone 49 . When 49 was treated with substoichiometric amounts of m CPBA at −45 °C preferentially the Δ 18 allylic alcohol was epoxidized to give tedanolide ( 1 ) 31. Unfortunately a separation of 49 and epoxide 1 via column chromatography was not successful, even when RP‐18 silica gel was used.…”
Section: Resultsmentioning
confidence: 99%
“…As the proposed configuration at C10–C14 (Scheme ) was based on the comparison of NMR data,9 we prepared the C9–C17 fragment 7 (Scheme ) to provide further support for this assignment. Methyl ( S )‐3‐hydroxy‐2‐methylpropionate ( 4 ) was converted to aldehyde 5 according to our previously reported route 2a. Utilization of a reaction sequence involving an Evans anti aldol reaction,6, 11 deprotection,12 and Wittig olefination efficiently converted aldehyde 5 to the allylic alcohol 6 .…”
Section: Methodsmentioning
confidence: 99%